Exploring the effect of hemp fibers’ addition on the properties of PLA/PPAd biodegradable blends - Eleftheria Xanthopoulou; Nikolaos Pardalis; Alexandra Zamboulis; Dimitrios N. Bikiaris (Sustainable Chemistry for the Environment)
Poly(lactic acid) (PLA) is a compostable aliphatic polymer with enhanced strength and toughness, and it is a promising material for packaging products. Polymer blending is a financially feasible and easy way to upgrade its properties, such as its slow degradation and crystallization rates and its modest elongation, and thus, make it more adaptable. Furthermore, the use of natural fibers as fillers can reinforce the biobased character of the final composite materials and enhance their antioxidant activity values, a crucial property of polymers that are addressed for active packaging. Herein, the influence of the addition of hemp fibers (HF) on the features of poly(lactic acid)/poly(propylene adipate) blends containing 85/15 w/w PLA/PPAd, was investigated. The utilization of a poly(lactic acid)-co-poly(propylene adipate) block copolymer (cop) as a compatibilizer was also examined. The thermal, morphological and mechanical assets of the composite materials were evaluated with the implementation of multiple techniques. The addition of HF enhanced the hydrophobicity and biodegradation of the composites, render them as candidates for several applications. Furthermore, the introduction of the compatibilizer successfully increases the adhesion between the polymeric matrices and the HF, resulting in enhanced properties.